PROSPECTS OF FUEL AND ENERGY RESOURCES IN UKRAINE DEVELOPMENT - Мітрахович, М.М.; Костюченко, Н.Ю. (Science-based technologies, 2009)
The analysis which were made shows the level of development of fuel and energy resources in Ukraine, the ways of development for the fuel and energy complex of the state are namely possible. The results of the conducted re-searches defined most perspective resources which are needed for providing of power safety in Ukraine, also al-ternative directions to the receipt of additional power mediums.